1997
DOI: 10.1006/viro.1996.8309
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Live-Attenuated Foot-and-Mouth Disease Virus as a Vaccine Candidate

Abstract: A variant of foot-and-mouth disease virus (FMDV) lacking the leader (L) coding region (A12-LLV2) was previously constructed and shown to be less virulent in cattle than its wild-type parent (A12-IC). In this study, cattle were tested for their clinical and immunological responses to subcutaneous inoculation with A12-LLV2 or A12-IC or to intramuscular vaccination with chemically inactivated A12-IC. Five weeks postinoculation animals were challenged by intradermal inoculation in the tongue with a virulent cattle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
66
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(71 citation statements)
references
References 2 publications
4
66
0
Order By: Relevance
“…As we have previously shown, L-deleted FMDVs are attenuated in their natural hosts, including swine and bovines (1,3,5,14). Their attenuation appears related to the inability to block synthesis of cytokines such as IFN-␣/␤ due to the absence of L proteinase activity.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…As we have previously shown, L-deleted FMDVs are attenuated in their natural hosts, including swine and bovines (1,3,5,14). Their attenuation appears related to the inability to block synthesis of cytokines such as IFN-␣/␤ due to the absence of L proteinase activity.…”
Section: Discussionmentioning
confidence: 84%
“…L proteinase also cleaves host translation initiation factor eIF-4G resulting in the shutoff of host cap-dependent mRNA translation (7,10,13,15). Consequently, FMDV RNA, which initiates translation in a cap-independent fashion via an internal ribosome entry site (IRES) and does not require intact eIF-4G, can freely use the host protein synthesis machinery for viral protein production (6,10,14,20,22).…”
mentioning
confidence: 99%
“…New attenuated virus vaccines have been designed by modification of infectious FMDV clones. Chimeric viruses in which the RGD receptor binding site [162] or the L gene [155] were deleted, induced protection in natural hosts without producing clinical symptoms. In spite of these promising results, the wide FMDV host-range and the high potential for variation of the virus make a careful study of the stability and pathogenicity of new recombinant vaccines necessary before they can be considered for field trials.…”
Section: Genetically-engineered Attenuated Strainsmentioning
confidence: 99%
“…L pro has also been shown to induce degradation of nuclear factor B (NF-B) in FMDV-infected cells, leading to inhibition of the host innate immune response (14,15). Numerous studies with genetically engineered serotype A FMDVs lacking L pro have been shown to be infectious but grow more slowly in cell culture (37) and is attenuated in both cattle and swine (5,7,26).…”
mentioning
confidence: 99%